3‐Arylidene‐N‐hydroxyoxindoles: A New Class of Compounds Endowed with Antitumor Activity. (17th June 2016) - Musso, Loana; Cincinelli, Raffaella; Zuco, Valentina; De Cesare, Michelandrea; Zunino, Franco; Fallacara, Anna Lucia; Botta, Maurizio; Dallavalle, Sabrina
Abstract: A series of compounds containing the N ‐hydroxyoxindole scaffold were synthesized and evaluated for antitumor activity. The compounds showed potent antiproliferative activity against the wild‐type p53 IGROV‐1 ovarian carcinoma cell line and considerably lower efficacy against the mutant IGROV‐1/Pt1 subline that lacks p53 function. The differential response of ovarian carcinoma cells depending on p53 status was also reflected in the varied susceptibility to apoptosis of the treated cell lines. These results support a role for the p53 transcription factor as a determinant of cytotoxicity. The therapeutic potential of the most promising compound of the series was evaluated in the treatment of an IGROV‐1 xenograft growing as ascitic tumor in mice. Using intraperitoneal administration, daily treatment with the compound for four weeks produced a significant delay in the onset of ascites. Abstract : Exploring new scaffolds : A series of 3‐arylidene‐ N ‐hydroxyoxindoles show potent antiproliferative and pro‐apoptotic activity against wild‐type p53 IGROV‐1 ovarian carcinoma cells and a considerably lower efficacy against the mutant IGROV‐1/Pt1 subline lacking p53 function. These results support a role for this transcription factor as a determinant of cytotoxicity. Treatment of an IGROV‐1 xenograft growing as an ascitic tumor produced a significant delay in the onset of ascites.